BIOINFORMATIC ANALYSIS OF SUBTILISIN-K2 FROM INDONESIAN MOROMI: EVALUATION OF ITS ANTITHROMBOTIC POTENTIAL FOR FUNCTIONAL FOOD APPLICATION - Fathma Syahbanu; Ratih Kurniasari; Linda Riski Sefrina; Muhammad Alfid Kurnianto (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Microbial fibrinolytic enzymes are commonly found in various fermented foods of both plant and animal origin. While extensive studies have been conducted in Japan, Korea, and China, research in Indonesia remains limited despite its rich diversity of fermented foods. Moromi, an intermediate product of soy sauce fermentation, contains Subtilisin-K2, an enzyme proven in vitro to degrade fibrin and fibrinogen, indicating potential antithrombotic activity. This study investigated the antithrombotic properties of Subtilisin-K2 using bioinformatic approaches, including molecular docking (HADDOCK) and molecular dynamics (GROMACS). Subtilisin-K2 exhibited strong binding affinities with fibrin, fibrinogen, PAI-1, PAI-2, and α-antiplasmin, with Gibbs free energy values of –19.4, –15.6, –15.7, –18.2, and –13.3 kcal/mol, respectively. Molecular dynamics confirmed the stability of these complexes. These findings suggest that Subtilisin-K2 from Indonesian moromi exhibits significant bioactivity, underscoring the potential of Indonesian fermented products as valuable sources of functional enzymes, especially as antithrombotic potential.